Características epidemiológicas, clínicas e virológicas de indivíduos diagnosticados com infecção recente pelo HIV no Centro de Testagem e Aconselhamento de Fortaleza - Guimarães, André Luiz Oliveira (2016)
AIDS is a pandemic disease consisting of an important public health problem worldwide. The suspicion of acute infection by HIV tends to be based on epidemiological data, clinical or laboratory, and typically confirmed by detection of seroconversion. The objective of this study was to investigate the individual characteristics and the isolated profile of individuals recent diagnosed with HIV-1 in the testing and counseling Center in Fortaleza, which obtained results in reagent in serology for HIV, as long as there was no previous knowledge of this serological status. An observational, cross-sectional and analytical study was carried out from October 2013 to September 2014. All recruited replied to a structured questionnaire with the aim of assessing the socioeconomic behavior profile. The presence of a recent infection was identified by the Bio-Rad avidity in a serological test and by the proportion of nucleotide ambiguities. Algorithms of multiple tests (MAAs) have been developed with the aim of improving the accuracy of detection. During the study period, 5469 users sought the CTA, being identified 258 positive exams, being recruited 108 participants. A recent infection was identified in 4.6% of individuals by the method of greed and in 61.9% by the proportion of ambiguity. The socio demographic profile behavior proved to be similar between the isolated techniques, as well as in the use of the MAAs, predominantly in young people between the ages 25 and 29 years, male, and exposure of risk of men who have sex with men. We found discrepancies between the values of CD4 with viral load and resistance transmitted. The prevalence of transmitted resistance of 9.5% and 87.6% of isolates belonging to subtype B were identified. The same data were found in patients with chronic infection. Since there is little data available that is related to this subject in our region, we believe that the study of the characteristics of individuals newly infected in our city, can allow the understanding of the epidemic in the city of Fortaleza-Ceará.